Forestry research: strategic insights for a health planet and thriving society - Piermaria Corona; Luigi Portoghesi; Susanna Nocentini (Annals of Silvicultural Research)
Research plays a pivotal role in driving methodological and technological advancements and translating them into practical applications, an endeavor especially crucial in an era defined by energy, digital, and demographic transitions. Through an interdisciplinary approach, forestry research should generate knowledge that supports policy-making, stimulates technological innovation, and promotes community engagement. The purpose of this note is to highlight several key aspects within this context. To that end, a commented discussion is provided, with particular emphasis on aspects related to silviculture and forest culture.